Moral injury: understanding Swedish veterans who are assessed but not diagnosed with PTSD - Grimell, Jan (Frontiers in Psychiatry, 2023)
This article is based on an interview study of 24 Swedish veterans who experienced deteriorating mental health and increased suffering without meeting the criteria for a PTSD diagnosis. With no clinical answers as to the cause of their deteriorating mental health, they have been thrown into a veteran's health limbo. The analysis was based on an inductive logic.A key finding of the analysis was a kind of deep-seated permanent moral conflict that could be conceptualised as moral injury. Such an injury can give rise to intense guilt, shame, anxiety, anger, dejection, bitterness, identity issues and more. The results section of the article details five different yet for the sample representative cases of moral injury and their implications. The notion of moral injury is linked to Mead's division of the self into an I and me, where me is the socially constructed part of the self that is charged with the morality of a group. Thus, a moral me played a key role in the development of moral injury. The conceptual apparatus illustrates a new way of understanding experiences that can create suffering and negatively impact a veteran's mental health. Future research is encouraged that examines this topic, national designs for addressing moral injury, screening for moral injury, and methods for healing included.